(untitled) (Research, Society and Development, 2022)
Cervical dentin hypersensitivity is a symptomatic phenomenon of difficult solution for the dental surgeon related to the dental clinic that has some predisposing factors such as non-carious cervical lesion, gingival recession, dental calculus and periodontal treatment. These factors can cause denudation of the tooth enamel surface and exposure of dentinal tubules, causing hypersensitivity. This was a cross-sectional observational study with random participation of 88 people, by collecting data through questionnaires and clinical examination. It aims to examine the prevalence of dentin hypersensitivity and its predisposing factors in patients seen at the Dentistry Clinic of Faculdades Integradas de Patos and Faculdades Unidas do Norte de Minas - Funorte, Campina Grande campus. From the clinical examinations and questionnaires, a high prevalence of dentin hypersensitivity was identified in the study population, and gingival recession, non-carious cervical lesion and tooth brushing three times or more during the day in a circular direction were considered important risk factors for HSDC. Furthermore, premolars were the teeth most affected with dentin hypersensitivity.